2018
DOI: 10.3390/md16120479
|View full text |Cite
|
Sign up to set email alerts
|

A Soft Coral-Derived Compound, 11-Dehydrosinulariolide, Induces G2/M Cell Cycle Arrest and Apoptosis in Small Cell Lung Cancer

Abstract: 11-Dehydrosinulariolide, an active compound that is isolated from the cultured soft coral Sinularia flexibilis, has been suggested to show anti-tumor biological characteristics according to previous studies. However, its potential effect on small cell lung cancer (SCLC) remains unknown. The present study investigates the underlying mechanism for the treatment of SCLC in vitro and in vivo. Cell viability was examined using the methyl-thiazol-diphenyl-tetrazolium (MTT) assay. Flow cytometry was applied to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Previous studies (14,40) have also indicated that the cell cycle pathway is an important pathway involved in the development and progression of SCLC. It has also been demonstrated that certain associated drugs can restore the abnormal cell cycle in SCLC, thus playing anti-tumor roles (41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (14,40) have also indicated that the cell cycle pathway is an important pathway involved in the development and progression of SCLC. It has also been demonstrated that certain associated drugs can restore the abnormal cell cycle in SCLC, thus playing anti-tumor roles (41).…”
Section: Discussionmentioning
confidence: 99%
“…Another pivotal mechanism that has contributed to the anti-tumor activity of chemotherapeutic drugs is cell cycle arrest, which accumulates cancer cells at a specific phase and halts the progress of the cell cycle (Lin et al, 2018). Our results showed that 9za could retard the cell population at G 0 /G 1 phase at low concentrations (<10 µM).…”
mentioning
confidence: 62%
“…Cancers are the consequence of cell-cycle dysregulation. Targeting the checkpoint signaling pathway, which generally leads to an arrest at the G1/S or G2/M phases, would be another effective therapeutic strategy [19]. Loss of MMP is closely linked to the activation of caspase-9, which plays a critical role in the initiation and maintenance of apoptosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle analysis was undertaken to classify the cell population into four distinctive phases, comprising the subG1 phase, G0/G1 phase, S phase, and G2/M phase. The subG1 population is an indication of apoptotic cell death, and the two checkpoints are G1/S and G2/M transitions [19]. As shown in Figure 1, Caco-2 cells showed a significant increase of population in the subG1 phase from around 4% in the case of control to approximately 15% and 31% when exposed to broccoli extracts for 24 and 48 h, respectively.…”
Section: Cytotoxic and Apoptotic Activitiesmentioning
confidence: 90%